Ação da sinvastatina sobre o diâmetro alveolar e a leucometria no líquido broncoalveolar de ratos em modelo de enfisema elastase-induzido - Jacobsen, Osneri (2009)
Pulmonary emphysema is characterized by reduction of lung parenchyma, which causes irreversible enlargement of the alveoli. It is, associated with chronic bronchitis, a manifestation of chronic obstructive pulmonary disease. Several mechanisms are involved in its development; presence of inflammatory cells into the lungs, imbalance between proteolytic and anti-proteolytic activity, apoptosis and oxidative stress. So far no therapy significantly reduces the inflammation and degeneration of emphysema. Simvastatin, an inhibitor of the enzyme 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase, used as hypocholesterolemic, has shown anti-inflammatory and antioxidant activity in recent studies that could reduce the deleterious effects of chronic inflammation related to emphysema. This study evaluated the effect of simvastatin on leukometry and pulmonary alveolar diameter involved in the development of elastase-induced emphysema in rats. Were used 24 male rats divided into 4 groups (n=6): control (C), emphysema (E), emphysema treated with simvastatin (ES) and group without emphysema treated with simvastatin (S). The ES and S groups received simvastatin (10 mg/kg), C and E received vehicle (CMC 0.2%) for 28 continuous days in single daily doses, by gavage. The animals were sacrificed and the biological samples collected at 28° day after initiation of treatment. Were quantified the number of leukocytes in bronchoalveolar fluid and the alveolar diameter of lung tissue. We also evaluated the direct inhibition of simvastatin over elastase and quantified the serum creatinekinase to evaluate the toxicity of the drug. The results showed that the 2 groups treated with simvastatin (S and ES) showed significant reduction of the leukocyte count (p <0.01) when compared to groups C and E. The evaluation of lung tissue, showed a significant increase in mean linear intercept (LM) of the emphysematous group compared to the control group and emphysema treated with simvastatin. The simvastatin is not a good inhibitor of elastase and did not induce toxicity in the dosage used. The results suggest that simvastatin reduces the inflammatory process involved in emphysema.